FINANCING STRATEGY FOR REJUVENATING PULP PAPER COMPANY (CASE STUDY: PT. XYZ) - Herlina Riz, Sri
Global demand growth in the pulp & paper industry showed an increase of 2.1%, signaling significant growth potential. PT XYZ, one of the world's largest pulp mills that has been in operation for 30 years, is currently facing a capital shortage that has resulted in a temporary suspension of operations. Given the opportunity of rising global demand for paper that is out of balance with paper production, PT. XYZ has the opportunity to restart its operations and fill the gap. Therefore, PT XYZ plans to implement a rejuvenation program to revive its business with the support of internal and external funding.